Cannabidiol promotes intestinal cholesterol uptake mediated by Pregnane X receptor - Brown, Conner; Kariuki, Wangeci; Zhong, Haizhen A.; Kippes, Audra; Sui, Yipeng (Frontiers in Endocrinology, 2024)
Cannabidiol (CBD), a non-psychoactive phytocannabinoid of cannabis, is therapeutically used as an analgesic, anti-inflammatory, and anti-psychotic drug. There is a growing concern about the adverse side effects posed by CBD usage. Pregnane X receptor (PXR) is a nuclear receptor activated by a variety of dietary steroids, pharmaceutical agents, and environmental chemicals. In addition to the role in xenobiotic metabolism, the atherogenic and dyslipidemic effects of PXR have been revealed in animal models. CBD has a low affinity for cannabinoid receptors, thus it is important to elucidate the molecular mechanisms by which CBD activates cellular signaling and to assess the possible adverse impacts of CBD on pro-atherosclerotic events in cardiovascular system, such as dyslipidemia. Our study aims to explore the cellular and molecular mechanisms by which exposure to CBD activates human PXR and increases the risk of dyslipidemia. Both human hepatic and intestinal cells were used to test if CBD was a PXR agonist via cell-based transfection assay. CBD was a selective agonist of PXR with higher activities on human PXR than rodents PXRs and promoted the dissociation of human PXR from nuclear co-repressors. The key amino acid residues Met246, Ser247, Phe251, Phe288, Trp299, and Tyr306 within PXR’s ligand binding pocket were identified to be necessary for the agonistic effects of CBD using computational docking study together with site-directed mutagenesis assay. The C57BL/6 wildtype mice were orally fed CBD in the presence of PXR antagonist resveratrol (RES) to determine how CBD exposure could change the plasma lipid profiles in a PXR-dependent manner. Exposure to CBD increased the circulating total cholesterol levels in mice which was partially caused by the induced expression levels of the key intestinal PXR-regulated lipogenic genes. Mechanistically, CBD induced the gene expression of key intestinal cholesterol transporters, which led to the increased cholesterol uptake by intestinal cells. Our study provides potential evidence for the future risk assessment of CBD on cardiovascular disease, such as dyslipidemia.